Bright Lights in the Desert : The Latter-day Saints of Las Vegas - Woods, Fred E. (Book collections on Project MUSE., 2022)
"Bright lights in the desert: the Latter-day Saints of Las Vegas explains how Latter-day Saints have shaped the metropolitan city which never sleeps by improving neighborhoods, inspiring educational institutions, bringing integrity to the marketplace, providing wholesome entertainment, cultural refinement, family stability, as well as community service"--